Piezoelectric polymer energy harvesting system fluctuating in a high speed wind-flow around a running electric vehicle. (20th November 2020) - Kim, Cheol; Park, Chang-min; Yoon, Jin-young; Park, Sang-young
Abstract: The battery of electric vehicles (EVs) is the only power source for the operation of an electric motor, heating and cooling devices, and many other auxiliaries. Therefore, the EV may be vulnerable to electricity shortage during running. It may be good if turbulent flow or vortex induced vibrations occurring around a vehicle body can be transformed into electricity by a piezoelectric energy harvester. In this study, an electric energy harvester has been developed in the forms of thin piezoelectric polymer beams and plates in order to supply auxiliary electric power for EV. The piezoelectric thin beam and plate can be installed as a grill structure or on the surface of a car while two edges of the harvesting structures are fixed and they fluctuate due to the various high-speed airflow-induced vibrations during running of the vehicle. The vortex shedding pressures around the piezoelectric systems and a whole car are computed on the basis of computational fluid dynamic transient analyses with FLUENT. The displacements and resulting voltages of energy harvesting structures are computed by using ANSYS piezoelectric finite element analyses which use the input loadings of the transient vortex shedding pressures obtained from CFD. As results of analyses, a reasonable amount of electric power applicable for the charge of an EV battery can be harvested from the passing wind around a vehicle. The 0.12 mm-thin PVDF beam-type (260 mm × 10 mm) and the plate-type (75 mm × 30 mm) generated the maximum 61.43 volt and 21.5 mW power and 4.77 volt and 0.191 mW at the air-speed of 90 km h −1 in the wind tunnel tests, respectively. The two types of harvesting systems installed on a car were also tested while driving the real car. The test results showed the good agreements with numerical predictions and wind tunnel test results.